Analisis Perencanaan Produksi Paving Dengan Menggunakan Metode Campbell Dudek Smith Dan Palmer Di CV. Daya Patra Sentosa - Novia Dwi Susanti; Endang Pudji Widjajati (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2023)
CV. Daya Patra Sentosa is a company that produces paving. Of the several types of products available, T6 paving, T8 paving, and hexagon paving are the types of products with the most demand. CV. Daya Patra Sentosa has problems in production scheduling, namely there are frequent delays in product delivery because they do not yet have an optimal production scheduling system and still use FCFS rules. The purpose of this study is to provide alternative production scheduling suggestions in order to obtain optimal production processing time and prevent delays in product delivery. These problems are solved by the method of Campbell Dudek Smith and Palmer. These two methods are compared to find out the production process time and get the optimal choice of production time. The calculation results show that the application of the method applied by the company, namely FCFS is 12342.9 minutes, the Campbell Dudek Smith method is 11953.9 minutes, and the Palmer method is 12023 minutes. It can be seen that the Campbell-Dudek-Smith method provides a shorter time of 389 minutes (3.15%) to the company's schedule.